2022
DOI: 10.1007/s10792-022-02289-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocular surface epithelial and stromal thicknesses in psoriasis using anterior segment optical coherence tomography

Abstract: Purpose: To evaluate the epithelial and stromal thicknesses of conjunctiva and cornea in psoriatic patients with anterior segment optical coherence tomography (AS-OCT), Methods: In this cross-sectional study, 61 patients with psoriasis and 42 age-matched, healthy individuals were enrolled. The epithelial and stromal thicknesses of both inferotemporal bulbar conjunctiva and central cornea were measured using AS-OCT.Results: Both the Tear break-up time and Schirmer-1 test values were signi cantly lower in the ps… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the study, corneal epithelium was measured manually from a single focus in the central cornea. 9 In our study, the mean epithelial thickness of the central 5 mm area of the cornea was analyzed, and no significant difference was determined between the psoriasis and control groups.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In the study, corneal epithelium was measured manually from a single focus in the central cornea. 9 In our study, the mean epithelial thickness of the central 5 mm area of the cornea was analyzed, and no significant difference was determined between the psoriasis and control groups.…”
Section: Discussionmentioning
confidence: 82%
“…12 Ersan et al reported that CCT measured with AS-OCT was significantly higher in psoriasis patients when compared to the control group. 9 As a result of these studies, it was revealed that corneal biomechanical properties were affected in various rheumatic diseases, even if no significant difference was detected in CCT. This shows us that the corneal morphology could alter without affecting the corneal thickness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Psoriasis has not shown an impact on ocular surface epithelial thickness. However, it may increase corneal stromal thickness [ 210 ]. CET was observed to increase in epidermolysis bullosa patients; the authors recommended using AS-OCT for corneal assessment to evaluate the effectiveness of new treatments in clinical trials [ 211 ].…”
Section: Systemic Conditionsmentioning
confidence: 99%